2022
DOI: 10.1088/1755-1315/1016/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Growth of soybean (Glycine max L.) on various types of biochar

Abstract: Climate change especially in agriculture, have a serious impact on soil fertility. Low soil fertility can affect the quality and quantity of agricultural produce. Biochar is one of the soil-fixing materials that can be used to increase soil fertility i.e. physical, chemical and biological fertility especially in vertisol soil. The purpose of this research was to find out the influence of various types of biochar and the best dose of biochar on the growth of soybean plants. The research was conducted at Screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Rice husk biochar has the ability to retain water and nutrients available to plants and is able to increase dry weight (Nurmalasari et al, 2022). High-rate biochar (12t/ ha) significantly increases the water holding capacity, available N (Fall et al, 2016), soluble P (Huang et al, 2018), and reduces N losses in the rhizosphere zone (Li et al, 2021).…”
Section: Plant Growthmentioning
confidence: 99%
“…Rice husk biochar has the ability to retain water and nutrients available to plants and is able to increase dry weight (Nurmalasari et al, 2022). High-rate biochar (12t/ ha) significantly increases the water holding capacity, available N (Fall et al, 2016), soluble P (Huang et al, 2018), and reduces N losses in the rhizosphere zone (Li et al, 2021).…”
Section: Plant Growthmentioning
confidence: 99%
“…Cow manure is able to improve the condition of the growing media chemically by providing additional nutrients and reducing N nutrient leaching [21]. Adding organic matter to the soil provides more nutrient than without treatment [22].…”
Section: Fresh Weight Of Biomassmentioning
confidence: 99%
“…Liu et al (2020) reported that 5% loading of biochar significantly recorded the highest soybean plant height, biomass and yield compared to the control and 10% biochar. Nurmalasari et al (2022) reported that 20 tons/ha of rice husk biochar increase plant height by 14.6% and 15 tons/ha increase leaves by 11.35% and number of branches by 36.65%. Similarly, Njoku et al (2015) reported that maize grain yield were significantly (p<0.05) higher in plots amended with biochar than the control.…”
Section: Number Of Branchesmentioning
confidence: 99%